Simple Additive Weighting as A Method of Decision Making Determine His Or Her Area Certification Applicants With No Senior High School District Tanggamus - Nadya Fitri Ayu Ningtias; Siti Mukodimah (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2019)
The teacher is one component which is in the school environment and which have important roles in one day of participants Teacher certification is a process to enhance performance or quality of teachers and then in competency test labor educator who where is the mechanism has been regulated by the government, that is going to the provision of certification labor educator who has qualified or standard professional. A support system of decision is a system that helps in decision making through model-model the decision to solve the problem is that are structured or structured .From 5 alternatives that in trials use 8 criteria for the results obtained teacher 4 who gain value from the calculation of the best use of simple additive weighting to determine teacher certification.